Legal Aspects of Foundation of Allied Assistance to Anti-Bolshevik Movement in Russia Exampled by the German Chancellor Baden’s Statement (Autumn of 1918) - M. M. Stelmak (Сибирское юридическое обозрение, 2014)
The article deals with the analysis of the emergence of the German Chancellor’s statement at the end of the First World War in the anti-Bolshevik gazette «Sibirsky Vestnik».